A temperature-based synthesis and characterization study of aluminum-incorporated diamond-like carbon thin films - Ghadai, Ranjan Kumar; Shanmugasundar, G.; Cepova, Lenka; Das, Soham; Kumar Mahto, Premchand; Kalita, Kanak (Frontiers in Mechanical Engineering, 2023)
The present work deals with the study of various properties of aluminum (Al)-incorporated diamond-like carbon (DLC) thin films synthesized using the atmospheric pressure chemical vapor deposition (APCVD) technique by varying the deposition temperature (Td) and keeping the N2 flow rate constant. Surface morphology analysis, resistance to corrosion, nanohardness (H), and Young’s modulus (E) of the coatings were carried out using atomic force microscopy (AFM), corrosion test, scanning electron microscopy (SEM), and nanoindentation test, respectively. SEM results showed a smoother surface morphology of the coatings grown at different process temperatures. With an increase in process temperature, the coating roughness (Ra) lies in the range of 20–36 µm. The corrosion resistance of the coating was found to be reduced with a consecutive increase in the deposition temperature from 800℃ to 880℃. However, above 880℃, the resistance increases further, and it may be due to the presence of more Al weight percentage in the coating. The nanoindentation result revealed that H and E of the coating increase with an increase in the CVD process temperature. The elastic–plastic property indicated by H/E and H3/E2, which are also indicators of the wear properties of the coating, were studied using the nanoindentation technique. The residual stresses (σ) calculated using Stoney’s equation revealed a reduction in residual stress with an increase in the process temperature.